قصۂ اصحابِ ِسبت: سر سید احمد خان، مفتی محمد عبدہ اور رشید رضا کی آرا کا مطالعہThe Story of Aṣḥab-e-Sabt: A Study of the Thoughts of Syed Ahmad Khan, Mufti Muhammad Abduh and Rashid Rida (Al-Qamar, 2021)
Sabt was a sacred day for Jews from the period of  Hazrat Musa. Almost 11 B.C Bani Israel lived near shore of Red sea, that town was called “Aylah”. These Bani Israel were economically civilized but morally declined. They were prohibited       praying for fish on Sabt, but they disobeyed this divine law and were punished and were made monkeys. There is controversy among exegetes whether Bani Israel were made monkeys physically or spiritually (Maskh Haqiqi or Maskh Man’vi), Sir Syed Ahmad Khan, Mufti Muhammad Abduh, and Syed Rashid Rida say this conversion was not physical. This tafsir was against the majority of the Mofasserin. After this some Urdu exegetes in subcontinent like Abdul Kalam Azad, Abdul Majid Darya Badi and Amin Ahsan Islahi gave the opinion that those bani Israel were not converted into real monkey but their deeds and minds were converted like monkeys and because of this they were lowered from animals and this was the lesson for other people generally and other Bani Israel especially. This article studies and concludes the opinions of Sir Syed, Abduh and Rashid Rida.
Keywords: Ashab-e-Sabt; Maskh; Haqiqi; Man’vi